Management of School-Community Relations - Karimah, Umi; Andini, Sekar Asti; Anggelia, Shilvy; Natalia, Natalia; Sutanto, Bahtiyar Heru (Literacy: Journal of Education and Social Science, 2023)
Schools and communities are two inseparable things. The community is expected to support and participate in the development of the educational process in schools. The research aims to describe the pattern of relationships between schools and society. In this case, the one who is in charge of being a bridge between the school and the community is a Public Relations. One of the roles of a Public Relations is to foster good relations with the community. Public relations officers must have a good attitude and be able to solve problems wisely. The importance of school and community relationships can achieve school goals. One of the goals of a public relations officer is to create a good image for his school and be able to influence the community to work together to realize a better quality education. In addition, a public relations officer has a well-organized planning function so that the goals and perfect implementation can be achieved. In the implementation of public relations, of course, there are challenges, therefore solutions and strategies are needed by improving the relationship between student guardians and the school.